2020
DOI: 10.21203/rs.2.23543/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep Deprivation Induces Neuroinflammation and Depressive-like Behaviors by Impairing the Regulation of Circadian Clock Genes Expression in Rats

Abstract: Background: Sleep loss leads to a spectrum of mood disorders such as anxiety, cognitive dysfunction and motor coordination impairment in many individuals. However, the underlying mechanisms are largely unknown. Methods: In this study, we examined the effects of sleep deprivation (SD) on depression and the mechanism by subjecting rats to a slowly rotating platform for 3 days to mimic the process of sleep loss. Sleep-deprived animals were tested behaviorally for anxiety- and depressive-like behaviors. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…These cytokines stimulate nonrestorative NREM sleep indicating a relationship between sleep and proinflammatory response together [139,140]. Recently, sleep deprivation in rats was demonstrated to directly cause neuroinflammation [141]. Interestingly, this study also showed an increase in AQP4 in sleep deprived rats.…”
Section: The Glial Systemsupporting
confidence: 48%
“…These cytokines stimulate nonrestorative NREM sleep indicating a relationship between sleep and proinflammatory response together [139,140]. Recently, sleep deprivation in rats was demonstrated to directly cause neuroinflammation [141]. Interestingly, this study also showed an increase in AQP4 in sleep deprived rats.…”
Section: The Glial Systemsupporting
confidence: 48%